THE QUESTIONING TECHNIQUES USED BY FOREIGN-EDUCATED BACKGROUND TEACHER TO PROMOTE CRITICAL THINKING - Irene Rosalina; Slamet Setiawan; Suhartono , (Department of English Language Education, UIN Sunan Ampel Surabaya, 2019)
Critical thinking is a cognitive skill that must be achieved by a student in higher education. By having critical thinking, especially in a language class, a student must understand the language and the message it brings to be communicated fluently and it will be a good asset for their future, especially to face the world of work. To foster students' critical thinking, a teacher is required to give them fairly complex questions with suitable questioning techniques. Asking the right technique is a good way to trigger critical thinking. This research uses a qualitative approach and focuses on indigenous teachers who have studied abroad as a subject. The teacher was chosen because, based on theory, overseas have felt a better critical thinking environment, have adapted and absorbed ways to be active in the classroom. This study aims to determine the types of questions and questioning techniques used by teachers to trigger critical thinking students. The results showed that the teacher used high-level cognitive questions namely the types of analysis (25, 3%), synthesis (21%) and evaluation (20, 3%). Then the questioning technique that most teachers use is the decomposition type (25%). It can be concluded that the teacher can foster students' critical thinking by providing high-level questioning techniques and questions with high cognitive levels